2009
DOI: 10.1007/978-1-60327-029-8_8
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle and Iron Chelators as a Potential Novel Alzheimer Therapy

Abstract: Current therapies for Alzheimer disease (AD) such as the acetylcholinesterase inhibitors and the latest NMDA receptor inhibitor, Namenda, provide moderate symptomatic delay at various stages of the disease, but do not arrest the disease progression or bring in meaningful remission. New approaches to the disease management are urgently needed. Although the etiology of AD is largely unknown, oxidative damage mediated by metals is likely a significant contributor since metals such as iron, aluminum, zinc, and cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 94 publications
0
71
0
Order By: Relevance
“…Recent reports demonstrated that PVPcoated NPs show vibrations by Fourier transform infrared spectroscopy spectra indicating the presence of C-N and carbonyl groups in the pyrrolidone ring (Borodko et al 2006;Pinkhasova et al 2012), and an overall negative charge is recorded in zeta potential measurements. In this study, the negative charge of PVPcoated NPs (AuNPs: -41.9 mV, PtNPs: -36.2 mV) ( Table) is a factor for MMP inhibition as we speculate that AuNPs or PtNPs directly chelate Zn 2+ in the MMP catalytic domain (Liu et al 2010;Tanakit et al 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Recent reports demonstrated that PVPcoated NPs show vibrations by Fourier transform infrared spectroscopy spectra indicating the presence of C-N and carbonyl groups in the pyrrolidone ring (Borodko et al 2006;Pinkhasova et al 2012), and an overall negative charge is recorded in zeta potential measurements. In this study, the negative charge of PVPcoated NPs (AuNPs: -41.9 mV, PtNPs: -36.2 mV) ( Table) is a factor for MMP inhibition as we speculate that AuNPs or PtNPs directly chelate Zn 2+ in the MMP catalytic domain (Liu et al 2010;Tanakit et al 2012).…”
Section: Discussionmentioning
confidence: 96%
“…As such, the dosage and the length of the treatments may be better monitored by individual intracellular zinc content. However, as recently performed in Alzheimer's disease to remove metals from the brain [83], the best results in COPD therapy might also be achieved using nanoparticles conjugated with synthetic MMP inhibitors that are directed at specific targets, such as MMPs in the lung, because the removal of zinc inactivates MMPs to nonfunctional apoenzyme [84].…”
Section: Role Of A-2 Macroglobulin (As Matrix Metalloproteases Inhibimentioning
confidence: 98%
“…As an example, desferrioxamine, a natural iron scavenger, is a specifi c chelator with a high affi nity for aluminum, copper, and zinc. Desferrioxamine is widely used in the treatment of AD (47). However, it requires continuous dosing due to its short circulating half-life.…”
Section: Iron Chelatorsmentioning
confidence: 99%